2007
DOI: 10.1002/jobm.200710325
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of salaceyin A against Colletotrichum orbiculare and Phytophthora capsici

Abstract: The antifungal activities of novel salicylic acid derivatives, salaceyin A, 6-(9-methyldecyl) salicylic acid, and salaceyin B, 6-(9-methylundecyl) salicylic acid were evaluated against plant pathogenic fungi. Salaceyin A showed antifungal activity against Cladosporium cucumerinum, Colletotrichum orbiculare and Phytophthora capsici at 64 microg ml(-1) while salaceyin B was less effective. In vitro antifungal activities of the compounds were influenced by the experimental pH value of the MIC test medium wherein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Antibacterial (Maruyama et al, 1975 et al, 1993) Salaceyin A A-254 Cytotoxic (Kim et al, 2006), antifungal (Park et al, 2007) Salaceyin B A-254 Cytotoxic (Kim et al, 2006), antifungal (Park et al, 2007) (Songia et al, 1997;Williamson et al, 2006) Virginiamycin M2…”
Section: Taxonomic Identification and Phylogenetic Analyses Of Bioactive Isolatesmentioning
confidence: 99%
“…Antibacterial (Maruyama et al, 1975 et al, 1993) Salaceyin A A-254 Cytotoxic (Kim et al, 2006), antifungal (Park et al, 2007) Salaceyin B A-254 Cytotoxic (Kim et al, 2006), antifungal (Park et al, 2007) (Songia et al, 1997;Williamson et al, 2006) Virginiamycin M2…”
Section: Taxonomic Identification and Phylogenetic Analyses Of Bioactive Isolatesmentioning
confidence: 99%
“…1) (Kim et al, 2006). Salaceyin A and B were originally isolated and characterized as antifungal and antitumor compounds (Kim et al, 2006;Park et al, 2007), but their mechanism of action is not known. A series of phenolic lipids compounds has been shown to inhibit bacterial, fungal, protozoan, and parasite growth, and this may be due to their interactions with proteins and/or on their membrane-disturbing properties (Stasiuk and Kozubek, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…They were also evaluated for antifungal activities against plant pathogenic fungi. Salaceyin A showed antifungal activity against Cladosporium cucumerinum, Colletotrichum orbiculare and Phytophthora capsici at 64 µg/mL, while salaceyin B was less effective (Park et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“… reported that Salaceyin A isolated from the culture broth of Streptomyces laceyi MS53 showed antifungal activity against P. capsici at 64 µg ml −1 for MIC. However, Staurosporine isolated from Streptomyces roseoflavus strain LS‐A24 completely inhibited the mycelial growth of P. capsici at 1 µg ml −1 for MIC .…”
Section: Discussionmentioning
confidence: 96%